2007
DOI: 10.1016/j.ibmb.2007.04.008
|View full text |Cite
|
Sign up to set email alerts
|

Sympatric Drosophila simulans flies with distinct mtDNA show age related differences in mitochondrial metabolism

Abstract: The primary causes of age related changes in mitochondrial metabolism are not known. The goal of this study is to document the influence of naturally occurring mtDNA variation on age dependent changes in mitochondrial respiration, hydrogen peroxide (H 2 O 2 ) generation and antioxidant defenses in the fly Drosophila simulans. Possible changes include an increase in rates of reactive oxygen species production with age and/or an age dependent decrease in antioxidant response. For this study we have used flies ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0
1

Year Published

2007
2007
2015
2015

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 69 publications
1
5
0
1
Order By: Relevance
“…Our study adds to a handful of studies demonstrating important functional phenotypic differences between sympatric mtDNA haplotypes, in vivo [ 13 , 26 – 28 , 39 ] as well as in vitro [ 40 42 ]. Collectively, this empirical body of research suggests that the long-standing view of segregating mtDNA variation as being selectively neutral may often be misplaced.…”
Section: Discussionmentioning
confidence: 75%
“…Our study adds to a handful of studies demonstrating important functional phenotypic differences between sympatric mtDNA haplotypes, in vivo [ 13 , 26 – 28 , 39 ] as well as in vitro [ 40 42 ]. Collectively, this empirical body of research suggests that the long-standing view of segregating mtDNA variation as being selectively neutral may often be misplaced.…”
Section: Discussionmentioning
confidence: 75%
“…In the longer‐lived genetic crosses, MnSOD and Cu/ZnSOD levels tended to be higher in females suggesting that bolstering SOD defenses may only be effective in compromised genetic backgrounds (Orr & Sohal, 2003). In contrast to these results, Katewa & Ballard 2007) compared ROS production in two groups of male D. simulans flies harboring distinct mtDNA haplogroups and found that ROS production differed in the two haplogroups but only one group showed an age‐dependent increase. Furthermore, several studies have failed to find any difference in rates of H 2 O 2 production in Drosophila , either with age (Miwa et al ., 2004), or between long‐lived diet‐restricted flies (Magwere et al ., 2006a), or in flies exhibiting high levels of activity (Magwere et al ., 2006b).…”
Section: Discussionmentioning
confidence: 93%
“…However, very few studies have explored phenotypic effects of sympatrically occurring mtDNA variants, which is unfortunate given that natural selection primarily acts within populations. In Drosophila simulans , sympatric mtDNA haplotypes do show differences in in vitro assays of metabolic function (Katewa & Ballard, ; Pichaud et al ., ). Similarly, Dowling et al .…”
Section: Introductionmentioning
confidence: 99%